THE EVALUATION OF THE RESULTS CEMENTLESS CORAIL TOTAL HIP ARTHROPLASTY IN PATIENTS YOUNGER THAN FIFTY WITH FEMORAL HEAD OSTEONECROSIS (Vietnam Journal of Community Medicine, 2022)
Objective: This study aimed to report the outcome of total hip arthroplasty (THA) with an extensivehydroxyapatite (HA) coating for the fixation of a tapered femoral stem (Corail) in patients youngerthan fifty years with osteonecrosis of the femoral head.Subject and method: Seventy-four osteonecrotic hips in fifty-eight patients were available forclinical and radiographic analyses at minimum follow-up of 10 years and at maximum follow-up 12years.Results: The mean Harris hip score improved from 41.68 ± 21,78 points preoperatively to 98.82 ±2.29 points at final follow-up. Seventy-four (100%) hips demonstrated stable bone ingrowth. No hipsshowed loosening or required revision for aseptic loosening.Conclusion: We believe that cementless THA with a Corail stem is a promising procedure for youngpatients with osteonecrosis of the femoral head.
Keywords: Osteonecrosis of the femoral head, total hip arthroplasty.